Ex-Ante Evaluation of India's Trade Alliance with Indo-Pacific Region: A General Equilibrium Analysis. Issue 2 (May 2023) - Srivastava, Archana; Mathur, Somesh Kumar; De, Prabir
The study attempts to analyse the economy-wide impact of Indo-Pacific alliance between India and rest of the 45 participating members using computable general equilibrium (CGE) model. We introduce four simulation scenarios in the general equilibrium model. The first scenario is the one in which India bilaterally liberalises trade in terms of both tariffs liberalisation alone and then removal of tariffs and reduction of non-tariff barriers together with all the countries of Indo-Pacific region. The second scenario is when India bilaterally liberalises trade with all the Asian countries of the Indo-Pacific region. The third scenario is when India bilaterally liberalises trade with all the countries of the Indo-Pacific region but excludes China from the region because of the current geopolitical reasons. The fourth scenario is the one when free trade is considered among all the countries in the Indo-Pacific region. The Indo-Pacific alliance seems to go beyond strategic alliance with the 46 Indo-Pacific participating countries, wherein the members gain due to potential movement of capital and welfare and economic gains because of tariff and non-tariff liberalisation among the member countries. The article suggests the road map for maximum welfare gains for India, keeping strategic and economic engagements with other member countries and sub-regions. JEL Code: F15